2004
DOI: 10.1016/j.femsec.2004.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of catalase and oxyR in the viable but nonculturable state of Vibrio vulnificus

Abstract: Vibrio vulnificus has proven difficult to culture from water or shellfish during winter months, which is attributed to the viable but nonculturable (VBNC) state. Because reactive oxygen species were found to be involved in the low temperature-induced entrance of V. vulnificus into this state, we generated an oxyR mutant which lacks catalase activity. This strain is nonculturable on solid media even at ambient temperature, due to the presence of H(2)O(2) in such media. Low temperature incubation of the parent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
113
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 56 publications
7
113
0
2
Order By: Relevance
“…Expression of these capsular genes during in situ incubation or during the VBNC state in V. vulnificus has not been reported. Previous work in our lab has shown that catalase activity in V. vulnificus decreases at low temperatures, and as a consequence, these cells are unable to defend against the hydrogen peroxide present in routine media and become nonculturable (16). However, during resuscitation at 20°C, catalase activity is restored, leading to a renewed culturable state.…”
mentioning
confidence: 87%
“…Expression of these capsular genes during in situ incubation or during the VBNC state in V. vulnificus has not been reported. Previous work in our lab has shown that catalase activity in V. vulnificus decreases at low temperatures, and as a consequence, these cells are unable to defend against the hydrogen peroxide present in routine media and become nonculturable (16). However, during resuscitation at 20°C, catalase activity is restored, leading to a renewed culturable state.…”
mentioning
confidence: 87%
“…As we have observed that Vibrio vulnificus cells in the VBNC state show significant culturability when agarose is substituted for agar as a solidifying agent (Kong et al 2004),…”
Section: Lb Agarose Platesmentioning
confidence: 97%
“…KatG is a primary peroxidase, a defense against reactive oxygen species (ROS), and apparently activates the first-line antituberculosis antibiotic isoniazid (28,53). We anticipate that KatG's retention in VBNC cells may be related to anti-ROS activity in stress survival or VBNC induction, as observed in V. vulnificus (54,55).…”
Section: Resultsmentioning
confidence: 99%